Territorial aspect of regional development in the new cohesion policy - Hajduga, Piotr (Terytorialny aspekt rozwoju regionalnego w nowej polityce spójności, 2014)
In the last ten-odd years we have been observing a discussion held in the European Union on the change of the regional policy paradigm in terms of its objectives, priorities, tools and the geographical scope of intervention. Changing development conditions require modification of the European cohesion policy model, the main priority of which still is to equalize the level of development of regions in the Community Member States. At the turn of the centuries we can see changes in the way the European cohesion policy is implemented and also the orientation of the equalization policy (which compensates the social and economic backwardness of regions) towards the development policy (which supports competitiveness, takes advantage of the endogenous potential for development and eliminates various barriers). Such policy is to contribute to a more effective use of the potential for development in the entire Community to stimulate growth, employment and cohesion. This paper aims at attracting attention to the evolution of the European cohesion policy model towards a place-based policy
Biblioteka Regionalisty, 2014, Nr 14, s. 39-50
Keywords: regional development; regional policy; cohesion policy; territorial cohesion; rozwój regionalny; polityka regionalna; polityka spójności; spójność terytorialna